Case Report: Sirolimus Alleviates Persistent Cytopenia After CD19 CAR-T-Cell Therapy - Xing, Limin; Wang, Yihao; Liu, Hui; Gao, Shan; Shao, Qing; Yue, Lanzhu; Liu, Zhaoyun; Wang, Huaquan; Shao, Zonghong; Fu, Rong (Frontiers in Oncology, 2021)
Chimeric antigen receptor T (CAR⁃T) cells show good efficacy in the treatment of relapsed and refractory B-cell tumors, such as acute B-cell leukemia (ALL) and diffuse large B-cell lymphoma (DLBCL). The main toxicities of CAR⁃T include cytokine release syndrome, immune effector cell- associated neurotoxicity syndrome, cytopenia, and severe infection. It is still very difficult for CAR⁃T to kill tumor cells to the maximum extent and avoid damaging normal organs. Here, we report a case of DLBCL with persistent grade 4 thrombocytopenia, and severe platelet transfusion dependence treated with CD19 CAR⁃T cells. We used sirolimus to inhibit the sustained activation of CAR⁃T cells and restore normal bone marrow hematopoiesis and peripheral blood cells. Moreover, sirolimus treatment did not affect the short-term efficacy of CAR⁃T cells, and DLBCL was in complete remission at the end of follow-up. In conclusion, sirolimus can represent a new strategy for the management of CAR-T cell therapy-related toxicity, including but not limited to hematotoxicity. However, further controlled clinical studies are required to confirm these fingdings.